The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.14569/ijacsa.2020.0110402
|View full text |Cite
|
Sign up to set email alerts
|

Issues and Challenges: Cloud Computing e-Government in Developing Countries

Abstract: Cloud computing has become essential for IT resources that can be delivered as a service over the Internet. Many e-government services that are used worldwide provide communities with relatively complex applications and services. Governments are still facing many challenges in their implementation of e-government services in general, including Saudi Arabia, such as poor IT infrastructure, lack of finance, and insufficient data security. This research paper investigates the challenges of e-government cloud serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 27 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…The study also found that the predictors can be divided into constructs or categories. Previous studies found that reliability and trust are important predictors of the usage of CBEG [20], [26]. Other studies refer to the importance of security in the usage of the CBEG [24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study also found that the predictors can be divided into constructs or categories. Previous studies found that reliability and trust are important predictors of the usage of CBEG [20], [26]. Other studies refer to the importance of security in the usage of the CBEG [24].…”
Section: Discussionmentioning
confidence: 99%
“…The trust and security of the CBEG were reviewed in the study of [19], and a model of trust security was proposed. The findings in the study of [20] indicated that infrastructure, availability and trust are critical for the use of CBEG. Mohammed et al [21] reviewed the literature and pointed out the lack of the studies on CBEG.…”
Section: Cbegmentioning
confidence: 98%
See 1 more Smart Citation
“…Frameworks and models have been proposed by several researchers for cloud computing in various e-services; For instance, the majority of the existing studies have discussed the potential benefits and possible drawbacks of adopting cloud computing in e-government. The researcher in a previous study published early between 2017 and 2020, [4,7,23,24]) reviewed the literature of the models which were proposed for e-government services migration to the cloud. The review analyzed and classified the models into two different types.…”
Section: Discussion Conclusion and Future Research Agendamentioning
confidence: 99%
“…Data was collected from 296 IT workers in the public sector in Yemen. According to Al Mudawi et al [24], the implementation of e-government in the public sector still faces many problems, with the main problems being lack of finance, poor IT infrastructure, and poor data security. This study focused on the issues facing the implementation of e-government cloud service models from the perspective of developing countries.…”
Section: Discussion Conclusion and Future Research Agendamentioning
confidence: 99%